Global epidemiological trends and variations in the burden of gallbladder cancer. Issue 5 (30th January 2017) - Are, Chandrakanth; Ahmad, Humera; Ravipati, Advaitaa; Croo, Darren; Clarey, Dillon; Smith, Lynette; Price, Ray R.; Butte, Jean M.; Gupta, Sameer; Chaturvedi, Arun; Chowdhury, Sanjib
Abstract : BACKGROUND: The aim of this study is to describe the trends and variations in the global burden of gallbladder cancer (GBC) with an emphasis on geographic variations and female gender. METHODS: Data (2012‐2030) relating to GBC was extracted from GLOBOCAN 2012 database and analyzed. RESULTS: The results of our study document a rising global burden of GBC with geographic and gender variations. The highest burden was noted in the WPRO region (based on WHO regions), Asia (based on continents) and India, Chile, and China (based on countries). The less developed regions of the world account for the majority of the global burden of GBC. The geographic variations are also present within individual countries such as in India and Chile. Females are afflicted at a much higher rate with GBC and this predilection is exaggerated in countries with higher incidence such as India and Chile. In females, people of certain ethnic groups and lower socio‐economic standing are at a higher risk. CONCLUSIONS: Our study demonstrates a rising global burden of GBC with some specific data on geographic and gender‐based variations which can be used to develop strategies at the global as well as the high‐risk individual country level.